Pembangunan Identitas Legal UMKM melalui Pendaftaran NIB di Desa Curahmalang - Evan Andarianto Ammaridho; Fina Ayu Ismawati; Halimatus Sa’dia; Ayunda Permata Dewi; Jaksa Prihasguna Trisardana (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The low level of business legality ownership among MSMEs in Curahmalang Village has limited their access to empowerment and financing programs. This community service activity aimed to build legal business identity through the registration of Business Identification Numbers (NIB). The methods included initial identification and education of MSME actors, technical assistance in registering through the Online Single Submission (OSS) system, and coordination and formal distribution of NIB documents at the village hall. The results indicate an increase in the number of MSMEs obtaining NIB as well as improved awareness and understanding of business legality. Qualitatively, the activity enhanced digital literacy and self-confidence among MSME actors. Therefore, direct and participatory assistance proved effective in accelerating business formalization and strengthening the village’s economic foundation sustainably.